Alloy Nanocrystals: Kinetically Controlled Growth of Polyhedral Bimetallic Alloy Nanocrystals Exclusively Bound by High‐Index Facets: Au–Pd Hexoctahedra (Small 5/2013). Issue 5 (4th March 2013) - Lee, Young Wook; Kim, Dongheun; Hong, Jong Wook; Kang, Shin Wook; Lee, Sang Bok; Han, Sang Woo
<x xml:space="preserve">Abstract</x> Manipulating the nanocrystal (NC) growth kinetics via control of the amount of reductant is the key synthetic lever to control the morphology of Au–Pd NCs. The alloys, which have a hexoctahedral structure enclosed exclusively by high‐index {541} facets, are prepared on page 660 by S. W. Han and co‐workers via the simultaneous reduction of Au and Pd precursors without seeds or additional metal ions as structure‐regulating agents. These NCs exhibit higher catalytic performances toward the electro‐oxidation of ethanol than Au–Pd alloy NCs bound by low‐index facets. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>